Extensiveness of Professional Development Opportunities by Heads of Schools in Enhancing Teachers’ Retention in Public Secondary Schools in Kilwa District Tanzania (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigated the extensiveness of professional development provided by heads of schools in enhancing teachers’ retention in public secondary schools in Kilwa District, Tanzania. The study was guided by Herzberg’s Two-Factor Theory, found by Frederick Herzberg in 1959. This study adopted a convergent design under a mixed methods approach. The target population of the study was 30 public secondary schools in Kilwa District, involving 386 teachers, 30 Heads of Schools (HoS), 1 District Secondary Education Officer (DSEO), 1 Assistance Secretary of Teachers Service Commission (TSC), and 1 District Executive Director (DED). The study employed probability and non-probability sampling techniques, including purposive and simple random sampling techniques. The sample size consisted of 10 secondary schools, 116 teachers, 10 HoS, 1 DSEO, 1 TSC, and 1 DED, making a total number of 126 respondents. Research instruments included questionnaires, interview guides, and document analysis guide. The validity of qualitative instruments was ensured by research experts from Educational Planning and Administration from MWECAU and reliability for quantitative instruments Cronbach’s Alpha technique was used to determine the internal consistency of the items, whereby coefficient for teacher’s questionnaire was 0.896. Data were analysed through frequencies, percentages, and means for Quantitative and through thematic analysis for Qualitative. The study revealed that professional development opportunities such as mentorship programs, in-service training, workshops, and collaborative learning opportunities are implemented by Head of Schools to a high extent in most schools in Kilwa District. The study concluded that Head of Schools provide Professional development opportunities such as regular training, mentorship career development support and indoor training which enhance teacher retention in public secondary schools in Kilwa district. Government through DED should ensure that teachers who actively engage in professional development are recognized and rewarded through promotions, salary increments, or other incentives to encourage long-term retention.